The Effect of Biocard Assisted Treffinger on Students' Creative Thinking Skills in Excretion System Materials - Siregar, Shopiah Dhuha; Lazuardi, Lazuardi (Jurnal Pendidikan MIPA, 2022)
This study aims to determine the effect of the Treffinger learning biocard. onstudents' creative thinking skills. This type of research is a quasi-experimental design with Nonquivalent Control Group. The study population was all class XI MIA SMAS PAB 8 Saentis with a sample of class XI MIA 2 as the experimental class taught with the Treffinger assisted by biocards and XI MIA 1 as the control class taught with the problem based learning model. The research instrument was a 20 item essay test of creative thinking skills on the excretory system material. Data analysis used descriptive statistical analysis and inferential statistical.analysis descriptive statistical showed that the average value of creative thinking skills of students who were taught using the Treffinger learning biocards was higher than the problem based learning model. analysis inferential statistical learning model Treffinger assisted by biocards effect on students' creative thinking skills. Keywords: creative thinking skills, Treffinger learning model, biocard, excretion system material. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp723-732